#SayHerName Loudly: How Black Girls Are Leading #BlackLivesMatter - Ileana Jiménez (Radical Teacher, 2016)
In the style of a black feminist roundtable, black girls at LREI (Little Red School House & Elisabeth Irwin High School), the famous progressive school from which Angela Davis was graduated in 1961, discuss the ways in which they are leading the #BlackLivesMatter movement by using an intersectional feminist lens to create poetry and film to resist systems of oppression and to #SayHerName as well as their own.